Strategi Pengembangan Unit Usaha Sayur Organik Di Kota Kediri (Studi Kasus Pada KWT Bangun Sejahtera) - Baha'udin (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2025)
The organic vegetable business is increasingly favored by entrepreneurs, including the Bangun Sejahtera Women Farmers Group (Kelompok Wanita Tani, KWT) in Kediri City. The promising potential in this sector has intensified competition, necessitating the formulation of strategic measures to ensure the sustainability and growth of KWT Bangun Sejahtera's organic vegetable enterprise. This study aims to: (1) Identify the internal and external factors influencing the development of the organic vegetable business and (2) Determine strategic approaches to enhance KWT Bangun Sejahtera's operations in Kediri City. The research employs a mixed-methods approach, with key informants selected through judgment sampling. Analytical tools include the IFE and EFE Matrices, Internal-External (IE) Matrix, Grand Strategy Matrix, SWOT analysis, and the Quantitative Strategic Planning Matrix (QSPM). The findings reveal ten key internal factors and eight key external factors. The most significant strength is